Activation and regulation of endogenous retroviral genes in the human pituitary gland and related endocrine tumours - Buslei, R.; Strissel, Pamela; Henke, Christine; Schey, Regina; Lang, Nadine; Ruebner, M.; Stolt, Claus; Fabry, Ben; Buchfelder, Michael; Strick, Reiner (Neuropathology and Applied Neurobiology, 2015)
Adenohypophysis (AH) hormone-producing cells represent the origin of diverse groups of pituitary adenomas (PA). Deregulation of hypothalamic hormone receptors, growth factors and cAMP signalling have been implicated in the aetiology of PA. Endogenous retroviruses (ERVs) are derived from past exogenous retroviral infections and represent more than 8% of the human genome. Some ERV genes encode open reading frames and produce functional proteins, for example, the ERVW-1 envelope gene Syncytin-1, essential for placentogenesis, but also deregulated in human tumours. Data concerning ERV expression in the AH and related endocrine tumours are missing.Syncytin-1 protein was analysed in normal AH (n = 15) and compared with five PA subtypes (n = 117) by immunohistochemistry. Absolute gene expression of 20 ERV functional envelope genes and ERVW-5 gag was measured. PA tissues were examined for Syncytin-1 and the cAMP signalling marker phospho-CREB-Ser133 using immunohistochemistry. Isolated primary human PA cells were treated with different hormones. Murine embryonic and adult pituitary gland ERV expressions were compared with human AH.Syncytin-1 protein colocalized with corticotropic cells of AH. In contrast, all PA demonstrated significant Syncytin-1 protein overexpression, supporting deregulation. All other ERV genes showed significant up-regulations in different PA subtypes. Phospho-CREB-Ser133 and Syncytin-1 colocalized in PA cells. Cultivated primary PA cells with ACTH or CRH induced their respective receptors and ERV genes. Syncytin-A/-B, murine orthologues to human Syncytin-1/-2, localized to embryonic and adult pituitary glands demonstrating functional mammalian conservation.Deregulated ERV genes may contribute to PA development via cAMP signalling.
EVALuna2:4955

ADSCs and adipocytes are the main producers in the autotaxin-lysophosphatidic acid axis of breast cancer and healthy mammary tissue in vitro - Schmid, Rafael; Wolf, Katharina; Robering, Jan Willem; Strauss, Selina; Strissel, Pamela; Strick, Reiner; Rübner, Matthias; Fasching, Peter; Horch, Raymund E.; Kremer, Andreas; Boos, Anja; Weigand, Annika (BMC Cancer, 2018)
BACKGROUND: Breast cancer is the most common malignancy in women affecting one out of eight females throughout their lives. Autotaxin (ATX) is upregulated in breast cancer which results in increased lysophosphatidic acid (LPA) formation within the tumor. This study's aim was to identify the role of different mammary cell populations within the ATX-LPA axis. METHODS: Epithelial-cell-adhesion-molecule-positive (EpCAM) and -negative cells from breast tumors, adipose-derived stem cells (ADSCs) of tumor-adjacent and tumor-distant mammary fat were isolated and compared to healthy ADSCs, mammary epithelial cells (HMECs), and mesenchymal cells (MES) of healthy mammary tissue (n = 4 each) and further to well-established breast (cancer) cell lines. RESULTS: mRNA expression analyses revealed that ADSCs and MES largely expressed LPA receptor 1 (LPAR1) while epithelial cells mainly expressed LPAR6. LPA 18:1 activated all the cell populations and cell lines by rise in cytosolic free calcium concentrations. MES and ADSCs expressed ATX whereas epithelial cells did not. ADSCs revealed the highest expression in ATX with a significant decline after adipogenic differentiation in healthy ADSCs, whereas ATX expression increased in ADSCs from tumor patients. Breast (cancer) cell lines did not express ATX. Transmigration of MES was stimulated by LPA whereas an inhibitory effect was observed in epithelial cells with no differences between tumors and healthy cells. Triple-negative breast cancer (TNBC) cell lines were also stimulated and the transmigration partly inhibited using the LPA receptor antagonist Ki16425. CONCLUSIONS: We here show that each mammary cell population plays a different role in the ATX-LPA axis with ADSCs and adipocytes being the main source of ATX in tumor patients in our experimental setting. Inhibitors of this axis may therefore present a valuable target for pharmacological therapies.
EVALuna2:35125

Akt and p53 are potential mediators of reduced mammary tumor growth by Chloroquine and the mTOR inhibitor RAD001 - Löhberg, Christian; Strissel, Pamela; Dittrich, Ralf; Strick, Reiner; Dittmer, Jürgen; Dittmer, Angela; Fabry, Ben; Kalender, Willi Alfred; Koch, Thorsten; Wachter, David; Groh, Nicole; Polier, Astrid; et al. (Biochemical Pharmacology, 2012)

Akt and p53 are potential mediators of reduced mammary tumor growth by Chloroquine and the mTOR inhibitor RAD001 - Löhberg, Christian; Strissel, Pamela; Dittrich, Ralf; Strick, Reiner; Dittmer, Jürgen; Dittmer, Angela; Fabry, Ben; Kalender, Willi Alfred; Koch, Thorsten; Wachter, David; Groh, Nicole; Polier, Astrid; et al. (Biochemical Pharmacology, 2012)

An Innovative Arteriovenous (AV) Loop Breast Cancer Model Tailored for Cancer Research - An, Ran; Strissel, Pamela; Al-Abboodi, Majida; Robering, Jan Willem; Reakasame, Supachai; Eckstein, Markus; Peddi, Ajay; Hauck, Theresa; Bäuerle, Tobias; Boccaccini, Aldo R.; Youssef, Almoatazbellah; Sun, Jiaming; et al. (Bioengineering, 2022)
Animal models are important tools to investigate the pathogenesis and develop treatment strategies for breast cancer in humans. In this study, we developed a new three-dimensional in vivo arteriovenous loop model of human breast cancer with the aid of biodegradable materials, including fibrin, alginate, and polycaprolactone. We examined the in vivo effects of various matrices on the growth of breast cancer cells by imaging and immunohistochemistry evaluation. Our findings clearly demonstrate that vascularized breast cancer microtissues could be engineered and recapitulate the in vivo situation and tumor-stromal interaction within an isolated environment in an in vivo organism. Alginate–fibrin hybrid matrices were considered as a highly powerful material for breast tumor engineering based on its stability and biocompatibility. We propose that the novel tumor model may not only serve as an invaluable platform for analyzing and understanding the molecular mechanisms and pattern of oncologic diseases, but also be tailored for individual therapy via transplantation of breast cancer patient-derived tumors.
CRIS-Team Scopus Importer:2022-07-15
Keywords: animal model; arteriovenous loop; breast cancer

Associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 with molecular subtypes, PD-L1 expression, and FGFR3 mutational status in two advanced urothelial bladder cancer cohorts - Bahlinger, Veronika; Branz, Annalena; Strissel, Pamela; Strick, Reiner; Lange, Fabienne; Geppert, Carol-Immanuel; Klümper, Niklas; Hölzel, Michael; Wach, Sven; Taubert, Helge; Sikic, Danijel; Wullich, Bernd; et al. (Histopathology, 2024)
Aims: Treatment options for advanced urothelial carcinoma (aUC) rapidly evolved: besides immunomodulative therapeutic options and inhibitors targeting Fibroblast growth factor receptor (FGFR) alterations, two new antibody-drug conjugates (ADC), sacituzumab govitecan (SG) and enfortumab vedotin (EV), have been approved. However, little is known about the associations of specific aUC properties and the surface target expression of TROP2 and NECTIN-4. Our aim was to characterize associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 protein and gene expression with morphomolecular and clinicopathological characteristics of aUC in two large independent cohorts. Methods and results: The TCGA BLCA (n = 405) and the CCC-EMN (n = 247) cohorts were retrospectively analysed. TROP2/TACSTD2 and NECTIN-4/NECTIN-4 are highly expressed at the protein and transcript level in aUC, and their expression status did not correlate with patient survival in both cohorts. NECTIN-4/NECTIN-4 expression was higher in luminal tumours and reduced in squamous aUCs. NECTIN-4 was negative in 10.6% of samples, and 18.4% of samples had low expression (H-score <15). The TROP2 negativity rate amounted to 6.5%. TACSTD2 and NECTIN-4 expression was reduced in neuroendocrine-like and/or protein-based double-negative tumours. TROP2- and NECTIN-4-negative tumours included one sarcomatoid and four neuroendocrine aUC. FGFR3 alterations and PD-L1 expression on tumour and immune cells did not associate with TROP2 or NECTIN-4 expression. Conclusions: TACSTD2/TROP2 and NECTIN-4/NECTIN-4 are widely expressed in aUC, independent of FGFR3 alterations or PD-L1 expression, thus representing a suitable target for ADC treatment in the majority of aUC. The expression loss was associated with aggressive morphomolecular aUC subtypes, i.e. neuroendocrine(-like) and sarcomatoid aUC.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Advanced urothelial carcinoma; membranous expression; NECTIN-4/NECTIN-4; TACSTD2/TROP2; treatment options

Bayesian model selection for complex dynamic systems - Mark, Christoph; Metzner, Claus; Lautscham, Lena; Strissel, Pamela; Strick, Reiner; Fabry, Ben (Nature Communications, 2018)
Time series generated by complex systems like financial markets and the earth's atmosphere often represent superstatistical random walks: on short time scales, the data follow a simple low-level model, but the model parameters are not constant and can fluctuate on longer time scales according to a high-level model. While the low-level model is often dictated by the type of the data, the high-level model, which describes how the parameters change, is unknown in most cases. Here we present a computationally efficient method to infer the time course of the parameter variations from time-series with short-range correlations. Importantly, this method evaluates the model evidence to objectively select between competing high-level models. We apply this method to detect anomalous price movements in financial markets, characterize cancer cell invasiveness, identify historical policies relevant for working safety in coal mines, and compare different climate change scenarios to forecast global warming.
EVALuna2:210064

Bladder tumor subtype commitment occurs in carcinoma in-situ driven by key signaling pathways including ECM remodeling - Wullweber, Adrian; Strick, Reiner; Lange, Fabienne; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Bertz, Simone; Weyerer, Veronika; Stöhr, Robert; Breyer, J.; Burger, M.; et al. (EUROPEAN UROLOGY, 2021)
CRIS-Team WoS Importer:2021-08-20

Bladder Tumor Subtype Commitment Occurs in Carcinoma In Situ Driven by Key Signaling Pathways Including ECM Remodeling - Wullweber, Adrian; Strick, Reiner; Lange, Fabienne; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Bertz, Simone; Weyerer, Veronika; Stöhr, Robert; Breyer, Johannes; Burger, Maximilian; et al. (Cancer Research, 2021)
Basal and luminal subtypes of invasive bladder tumors have significant prognostic and predictive impacts for patients. However, it remains unclear whether tumor subtype commitment occurs in noninvasive urothelial lesions or in carcinoma in situ (CIS) and which gene pathways are important for bladder tumor progression. To understand the timing of this commitment, we used gene expression and protein analysis to create a global overview of 36 separate tissues excised from a whole bladder encompassing urothelium, noninvasive urothelial lesions, CIS, and invasive carcinomas. Additionally investigated were matched CIS, noninvasive urothelial lesions, and muscle-invasive bladder cancers (MIBC) from 22 patients. The final stage of subtype commitment to either a luminal or basal MIBC occurred at the CIS transition. For all tissues combined, hierarchical clustering of subtype gene expression revealed three subtypes: "luminal," "basal," and a "luminal p53-/extracellular matrix (ECM)-like" phenotype of ECM-related genes enriched in tumor-associated urothelium, noninvasive urothelial lesions, and CIS, but rarely invasive, carcinomas. A separate cohort of normal urothelium from noncancer patients showed significantly lower expression of ECM-related genes compared with tumor-associated urothelium, noninvasive urothelial lesions, and CIS. A PanCancer Progression Panel of 681 genes unveiled pathways specific for the luminal p53-/ECM-like cluster, for example, ECM remodeling, angiogenesis, epithelial-to-mesenchymal transition, cellular discohesion, cell motility involved in tumor progression, and cell proliferation and oncogenic ERBB2/ERBB3 signaling for invasive carcinomas. In conclusion, this study provides insights into bladder cancer subtype commitment and associated signaling pathways, which could help predict therapy response and enhance our understanding of therapy resistance.
CRIS-Team WoS Importer:2021-04-09

Brain and breast cancer cells with pten loss of function reveal enhanced durotaxis and rhob dependent amoeboid migration utilizing 3d scaffolds and aligned microfiber tracts - Wieland, Annalena; Strissel, Pamela; Schorle, Hannah; Bakirci, Ezgi; Janzen, Dieter; Beckmann, Matthias; Eckstein, Markus; Dalton, Paul D.; Strick, Reiner (Cancers, 2021)
Background: Glioblastoma multiforme (GBM) and metastatic triple-negative breast cancer (TNBC) with PTEN mutations often lead to brain dissemination with poor patient outcome, thus new therapeutic targets are needed. To understand signaling, controlling the dynamics and mechanics of brain tumor cell migration, we implemented GBM and TNBC cell lines and designed 3D aligned microfibers and scaffolds mimicking brain structures. Methods: 3D microfibers and scaffolds were printed using melt electrowriting. GBM and TNBC cell lines with opposing PTEN genotypes were analyzed with RHO-ROCK-PTEN inhibitors and PTEN rescue using live-cell imaging. RNA-sequencing and qPCR of tumor cells in 3D with microfibers were performed, while scanning electron microscopy and confocal microscopy addressed cell morphology. Results: In contrast to the PTEN wildtype, GBM and TNBC cells with PTEN loss of function yielded enhanced durotaxis, topotaxis, adhesion, amoeboid migration on 3D microfibers and significant high RHOB expression. Functional studies concerning RHOB-ROCK-PTEN signaling confirmed the essential role for the above cellular processes. Conclusions: This study demonstrates a significant role of the PTEN genotype and RHOB expression for durotaxis, adhesion and migration dependent on 3D. GBM and TNBC cells with PTEN loss of function have an affinity for stiff brain structures promoting metastasis. 3D microfibers represent an important tool to model brain metastasizing tumor cells, where RHO-inhibitors could play an essential role for improved therapy.
CRIS-Team Scopus Importer:2021-10-29
Keywords: 3D microfiber; 3D tumor model; Amoeboid cell migration; Brain cancer; Breast cancer; Durotaxis; PTEN; RHO; ROCK; Topotaxis

Breast Tumor Cell Survival and Morphology in a Brain-like Extracellular Matrix Depends on Matrix Composition and Mechanical Properties - Türker, Esra; Andrade Mier, Mateo S.; Faber, Jessica; Padilla Padilla, Selma J.; Murenu, Nicoletta; Stahlhut, Philipp; Lang, Gregor; Lamberger, Zan; Weigelt, Jeanette; Schaefer, Natascha; Tessmar, Jörg; Strissel, Pamela; et al. (Advanced Biology, 2024)
Triple-negative breast cancer (TNBC) is the most invasive type of breast cancer with high risk of brain metastasis. To better understand interactions between breast tumors with the brain extracellular matrix (ECM), a 3D cell culture model is implemented using a thiolated hyaluronic acid (HA-SH) based hydrogel. The latter is used as HA represents a major component of brain ECM. Melt-electrowritten (MEW) scaffolds of box- and triangular-shaped polycaprolactone (PCL) micro-fibers for hydrogel reinforcement are utilized. Two different molecular weight HA-SH materials (230 and 420 kDa) are used with elastic moduli of 148 ± 34 Pa (soft) and 1274 ± 440 Pa (stiff). Both hydrogels demonstrate similar porosities. The different molecular weight of HA-SH, however, significantly changes mechanical properties, e.g., stiffness, nonlinearity, and hysteresis. The breast tumor cell line MDA-MB-231 forms mainly multicellular aggregates in both HA-SH hydrogels but sustains high viability (75%). Supplementation of HA-SH hydrogels with ECM components does not affect gene expression but improves cell viability and impacts cellular distribution and morphology. The presence of other brain cell types further support numerous cell–cell interactions with tumor cells. In summary, the present 3D cell culture model represents a novel tool establishing a disease cell culture model in a systematic way.
CRIS-Team Scopus Importer:2024-07-19
Keywords: breast tumor cells; co-cultures; hyaluronic acid; Matrigel; PCL scaffolds

Circulating micro-RNAs as potential blood-based markers for early stage breast cancer detection - Schrauder, Michael G.; Strick, Reiner; Schulz-Wendtland, Rüdiger; Strissel, Pamela; Kahmann, Laura; Loehberg, Christian R.; Lux, Michael P.; Jud, Sebastian; Hartmann, Arndt; Hein, Alexander; Bayer, Christian M.; Bani, Mayada; et al. (PLoS ONE, 2012)
Introduction: MicroRNAs (miRNAs, miRs) are a class of small, non-coding RNA molecules with relevance as regulators of gene expression thereby affecting crucial processes in cancer development. MiRNAs offer great potential as biomarkers for cancer detection due to their remarkable stability in blood and their characteristic expression in many different diseases. We investigated whether microarray-based miRNA profiling on whole blood could discriminate between early stage breast cancer patients and healthy controls. Methods: We performed microarray-based miRNA profiling on whole blood of 48 early stage breast cancer patients at diagnosis along with 57 healthy individuals as controls. This was followed by a real-time semi-quantitative Polymerase Chain Reaction (RT-qPCR) validation in a separate cohort of 24 early stage breast cancer patients from a breast cancer screening unit and 24 age matched controls using two differentially expressed miRNAs (miR-202, miR-718). Results: Using the significance level of p<0.05, we found that 59 miRNAs were differentially expressed in whole blood of early stage breast cancer patients compared to healthy controls. 13 significantly up-regulated miRNAs and 46 significantly down-regulated miRNAs in our microarray panel of 1100 miRNAs and miRNA star sequences could be detected. A set of 240 miRNAs that was evaluated by radial basis function kernel support vector machines and 10-fold cross validation yielded a specificity of 78.8%, and a sensitivity of 92.5%, as well as an accuracy of 85.6%. Two miRNAs were validated by RT-qPCR in an independent cohort. The relative fold changes of the RT-qPCR validation were in line with the microarray data for both miRNAs, and statistically significant differences in miRNA-expression were found for miR-202. Conclusions: MiRNA profiling in whole blood has potential as a novel method for early stage breast cancer detection, but there are still challenges that need to be addressed to establish these new biomarkers in clinical use. © 2012 Schrauder et al.
CRIS-Team Scopus Importer:2021-07-19

Collective forces of tumor spheroids in three-dimensional biopolymer networks - Mark, Christoph; Grundy, Thomas J.; Strissel, Pamela; Böhringer, David; Grummel, Nadine; Gerum, Richard; Steinwachs, Julian; Hack, Carolin; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner; O'Neill, Geraldine M.; et al. (eLife, 2020)
We describe a method for quantifying the contractile forces that tumor spheroids collectively exert on highly nonlinear three-dimensional collagen networks. While three-dimensional traction force microscopy for single cells in a nonlinear matrix is computationally complex due to the variable cell shape, here we exploit the spherical symmetry of tumor spheroids to derive a scale-invariant relationship between spheroid contractility and the surrounding matrix deformations. This relationship allows us to directly translate the magnitude of matrix deformations to the total contractility of arbitrarily sized spheroids. We show that our method is accurate up to strains of 50% and remains valid even for irregularly shaped tissue samples when considering only the deformations in the far field. Finally, we demonstrate that collective forces of tumor spheroids reflect the contractility of individual cells for up to 1 hr after seeding, while collective forces on longer timescales are guided by mechanical feedback from the extracellular matrix.
CRIS-Team WoS Importer:2020-05-22

Collective Synchronization of Contractile Forces in Tumor Spheroids - Böhringer, David; Mark, Christoph; Grummel, Nadine; Strissel, Pamela; Strick, Reiner; Grundy, Thomas J.; O'Neill, Geraldine M.; Fabry, Ben (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

Comparative analysis of tumour mutational burden (TMB) prediction methods and its association with determinants of the tumour immune microenvironment of urothelial bladder cancer (UBC) - Eckstein, Markus; Hartmann, Arndt; Strissel, Pamela; Strick, Reiner; Wach, S.; Taubert, Helge; Wullich, Bernd; Geppert, Carol-Immanuel; Weyerer, Veronika; Stöhr, Robert; Rübner, Matthias; Fasching, Peter; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Comparison of Whole Ovary Cryotreatments for Fertility Preservation - Lotz, Laura; Hauenstein, Tanja; Nichols-Burns, S. M.; Strissel, Pamela; Hoffmann, I.; Findeklee, S.; Dittrich, Ralf; Beckmann, Matthias; Oppelt, Patricia (Reproduction in Domestic Animals, 2015)
The goal of this study was to compare a traditional slow-freeze method (TF) with an open unidirectional slow freeze cooling system (UF) for whole ovary cryopreservation. Therefore, whole pig ovaries were randomly assigned to (A) fresh control, (B) traditional slow freeze (TF) or (C) unidirectional slow freeze (UF). Ovaries were perfused with 10% DMSO in Krebs-Ringer. For TF, whole ovaries were placed in specimen jars containing 10% DMSO and placed into a specialized container for freezing filled with propan-2-ol. For UF, whole ovaries were placed within a specially designed container containing 10% DMSO and transferred to a specialized freezing machine (CTE 920). Histological evaluation demonstrated intact morphology of follicles in all groups; however, an overall decrease of follicle numbers in TF (46%) and UF (50%) compared to fresh control. Live/dead assay indicated significantly lower populations of live cells in both TF (60%) and UF (58%) compared to fresh tissue (74%). TUNEL assay confirmed a difference in percentage of apoptotic follicles between fresh and TF, but there was no significant difference between fresh and UF. To improve the structural and functional integrity of whole ovaries, further investigation, especially into directional freezing, is needed. Whole ovary cryopreservation could provide opportunities for women facing fertility loss due to chemo- or radiotherapy treatment.
EVALuna2:17545

Correction: Collective forces of tumor spheroids in three-dimensional biopolymer networks. - Mark, Christoph; Grundy, Thomas J.; Strissel, Pamela; Böhringer, David; Grummel, Nadine; Gerum, Richard; Steinwachs, Julian; Hack, Carolin; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner; O'Neill, Geraldine M.; et al. (eLife, 2020)
EVALuna2:417751

Cullin 7 and Fbxw 8 expression in trophoblastic cells is regulated via oxygen tension: Implications for intrauterine growth restriction - Fahlbusch, Fabian; Dawood, Yousif Louay; Hartner, Andrea; Menendez-Castro, Carlos; Nögel, Stephanie; Tzschoppe, Anja; Schneider, Holm; Strissel, Pamela; Beckmann, Matthias; Schleussner, Ekkehard; Rübner, Matthias; Dörr, Helmuth-Günther; et al. (Journal of Maternal-Fetal & Neonatal Medicine, 2012)
Objective: The F-box protein Fbxw8 is a cofactor of Cullin 7 (Cul7), which regulates protein transfer to the proteasome and cell growth. Cul7 or Fbxw8 deficiency is associated with intrauterine growth restriction (IUGR) due to abnormal placental development leading to poor oxygen supply to the fetus. We studied the role of hypoxia for Fbxw8 and Cul7 expression in trophoblastic cells. Methods: Immunomagnetic bead-separated extravillous trophoblast (EVT) and villous trophoblast (VT) and trophoblast cell lines were incubated with 1 or 8% O2. Fbxw8 and Cul7 expression was determined in IUGR versus matched control placentas. Results: Fbxw8 was expressed uniformly in trophoblasts, whereas Cul7 expression was most prominent in trophoblast cell lines. Hypoxia reduced expression of Cul7 and Fbxw8 in all trophoblastic cells, except for villous trophoblasts. In vivo, Cul7 and Fbxw8 were detected in syncytiotrophoblast cells, VT, and EVT cells. Although no significant changes in expression levels of Fbxw8 or Cul7 were noted in IUGR compared with control placentas, Fbxw8 expression correlated negatively with gestational age in the control, but not in the IUGR group. Conclusion: Fbxw8 and Cul7 expression reveals a complex regulation in trophoblastic cells. Our findings suggest that dysregulation of Cul7 and Fbxw8 expression might affect trophoblast turnover in IUGR. © 2012 Informa UK, Ltd.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Cul7; Fbxw8; IUGR; Oxygen; Placenta; Trophoblast

Cytotoxic T-cell-related gene expression signature predicts improved survival in muscle-invasive urothelial bladder cancer patients after radical cystectomy and adjuvant chemotherapy - Eckstein, Markus; Strissel, Pamela; Strick, Reiner; Weyerer, Veronika; Wirtz, Ralph; Pfannstiel, Carolin; Wullweber, Adrian; Lange, Fabienne; Erben, Philipp; Stöhr, Robert; Bertz, Simone; Geppert, Carol-Immanuel; et al. (Journal for ImmunoTherapy of Cancer, 2020)
Background Assessment of the immune status of muscle-invasive bladder cancer (MIBC) has previously shown to be prognostically relevant after treatment with curative intent. We conducted this study to develop a clinically applicable immune gene expression assay to predict prognosis and adjuvant chemotherapy benefit. Patients and methods Gene expression of CD3Z, CD8A and CXCL9, immune cell (IC) populations including stromal tumor infiltrating lymphocytes (sTILs), T-cells, natural killer cells (NK-cells), macrophages, Programmed cell death protein 1 positive (PD-1) IC and tumor subtypes (MD Anderson Cancer Center/MDACC-approach) were assessed in 187 MIBC patients (Comprehensive Cancer Center Erlangen-EMN/CCC-EMN-cohort). A gene expression signature was derived by hierarchical-clustering and validated in The Cancer Genome Atlas (TCGA)-cohort. IC populations in the TCGA cohort were assessed via CIBERSORT. Benefit of platinum-containing adjuvant chemotherapy was assessed in a pooled cohort of 125 patients. Outcome measurements were disease specific survival, disease-free survival and overall survival. Results The gene expression signature of CXCL9, CD3Z and CD8A correlates with quantitative amounts of specific IC populations and sTILs (CCC-EMN: ρ-range: 0.44-0.74; TCGA: ρ-range: 0.56-0.82) and allows stratification of three different inflammation levels (inflamed high, inflamed low, uninflamed). Highly inflamed tumors are preferentially basal subtype and show favorable 5-year survival rates of 67.3% (HR=0.27; CCC-EMN) and 55% (HR=0.41; TCGA). Uninflamed tumors are predominantly luminal subtypes and show low 5-year survival rates of 28% (CCC-EMN) and 36% (TCGA). Inflamed tumors exhibit higher levels of PD-1 and Programmed cell death 1 ligand 1 (PD-L1). Patients undergoing adjuvant platinum-based chemotherapy with 'inflamed high' tumors showed a favorable 5-year survival rate of 64% (HR=0.27; merged CCC-EMN and TCGA cohort). Conclusion The gene expression signature of CD3Z, CD8A and CXCL9 can assess the immune status of MIBC and stratify the survival of MIBC patients undergoing surgery and adjuvant platinum-based chemotherapy. Furthermore, the assay can identify patients with immunological hot tumors with particular high expression of PD-L1 potentially suitable for immunotherapy.
CRIS-Team Scopus Importer:2020-06-05
Keywords: immunology; pathology; urology

DESIGN OF IN VITRO CULTURE SYSTEM USING MELT ELECTROWRITING - Bakirci, Ezgi; Hrynevich, Andrei; Schaefer, Natascha; Janzen, Dieter; Wieland, Annalena; Dahri, Ouafa; Kim, Jaehyeon; Ceballos, Estaban; Strissel, Pamela; Strick, Reiner; Villmann, Carmen; Dalton, Paul D. (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

Development of an Innovative Cell Isolation Method for the Investigation of Breast Cancer Pathogenesis and Angiogenesis for Experimental In Vitro And In Vivo Assays - Weigand, Annika; Tasbihi, Kereshmeh; Strissel, Pamela; Strick, Reiner; Horch, Raymund E.; Boos, Anja (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2017)
Background Breast cancer is the world's most common cancer among women. Autologous lipotransfer is increasingly used for breast reconstruction following surgical removal of the tumour. In cell-assisted lipotransfer, the transplant is enriched with stem cells from adipose tissue (ADSC). Despite positive clinical results, there are some concerns regarding oncological safety due to transplanted stem cells. To date there are only a few breast cancer studies using primary cells from the same patient to enable further investigation into the complexity of cell-cell interactions in breast cancer in an experimental setting.Materials and methodsWe performed literature research on the topic of autologous lipotransfer. 5 different cell types (epithelial, mesenchymal cells, ADSC, endothelial cells, endothelial progenitor cells) were isolated from mammary (carcinoma) tissue or blood and were subsequently characterised for gene and protein expression as well as functional properties. The arteriovenous (AV) loop model in the rat was evaluated as a possible in vivo model for breast cancer pathogenesis and angiogenesis in this study.ResultsThe literature provided evidence for an in-vitro interaction between ADSC and cells of the mammary (carcinoma) tissue. In some clinical studies, certain subgroups of patients appeared to be exposed to an increased risk of tumour recurrence after lipotransfer, but in most studies no correlation between lipotransfer and tumour recurrence was found. Different cell populations, which differed significantly in terms of surface markers, gene expression and functional properties, were isolated from tissue of the same patient. Axial vascularised tissue was successfully generated in the AV loop model.ConclusionIn this study we were able to isolate different cell populations from the same patient, which reflect the heterogeneity of the tumour tissue. This enables a precise analysis of cell-cell interactions and their effects on tumour angiogenesis and pathogenesis in breast cancer. In combination with the AV loop model, this offers new possibilities to generate vascularised mammary carcinoma tissue as well as healthy mammary gland tissue in vivo as an optimal model for the clinical setting.
EVALuna2:32854

Endogenous Retroviral-K Envelope Is a Novel Tumor Antigen and Prognostic Indicator of Renal Cell Carcinoma - Weyerer, Veronika; Strissel, Pamela; Stohr, Christine; Eckstein, Markus; Wach, Sven; Taubert, Helge; Brandl, Lisa; Geppert, Carol-Immanuel; Wullich, Bernd; Cynis, Holger; Beckmann, Matthias; Seliger, Barbara; et al. (Frontiers in Oncology, 2021)
Renal cell carcinoma (RCC) is one of the ten most common cancers for men and women with an approximate 75% overall 5-year survival. Sixteen histological tumor subtypes exist and the most common are papillary, chromophobe and clear cell renal cell carcinoma (ccRCC) representing 85% of all RCC. Although epigenetically silenced, endogenous retroviral (ERV) genes become activated in tumors and function to ignite immune responses. Research has intensified to understand ERV protein function and their role as tumor antigens and targets for cancer (immune) therapy. ERV-K env is overexpressed and implicated as a therapeutic target for breast cancer, however studies in RCC are limited. In this investigation a human RCC tissue microarray (TMA) (n=374) predominantly consisting of the most common histological tumor subtypes was hybridized with an ERV-K env antibody and correlated with patient clinical data. TMA results showed the highest amount of ERV-K env protein expression and the strongest significant membrane expression in ccRCC versus other RCC subtypes. High ERV-K env total protein expression of all tumor subtypes significantly correlated with low tumor grading and a longer disease specific survival using multivariable analyses. Cell proliferation and invasion were assayed using the kidney cell lines HEK293 with wild-type p53 and a ccRCC cell line MZ1257RC mutated for p53. Transfecting these cell lines with a codon optimized ERV-K113 env overexpressing CMV vector was performed with or without 5'-Aza-2'-deoxycytidine (Aza) treatment to sustain promoter de-methylation. MZ1257RC showed induction of ERV-K113 expression and significantly increased both proliferation and invasion in the presence or absence of Aza. HEK293 cells demonstrated a restriction of ERV-K113 env expression and invasion with no changes in proliferation in the absence of Aza. However, in the presence of Aza despite increased ERV-K113 env expression, an inhibition of HEK293 proliferation and a further restriction of invasion was found. This study supports ERV-K env as a single prognostic indicator for better survival of RCC, which we propose represents a new tumor antigen. In addition, ERV-K env significantly regulates proliferation and invasion depending on p53 status and Aza treatment.
CRIS-Team WoS Importer:2021-05-14
Keywords: tumor antigen; renal cell carcinoma; patient prognosis; p53; ERV-K; invasion; azacytidine; endogenous retrovirus

Epigenetic Therapies in Ovarian Cancer Alter Repetitive Element Expression in a TP53-Dependent Manner - Mcdonald, James; Diab, Noor; Arthofer, Elisa; Hadley, Melissa; Kanholm, Tomas; Rentia, Uzma; Gomez, Stephanie; Yu, Angela; Grundy, Erin E.; Cox, Olivia; Topper, Michael J.; Xing, Xiaoyun; et al. (Cancer Research, 2021)
Epithelial ovarian carcinomas are particularly deadly due to intratumoral heterogeneity, resistance to standard-of-care therapies, and poor response to alternative treatments such as immunotherapy. Targeting the ovarian carcinoma epigenome with DNA methyltransferase inhibitors (DNMTi) or histone deacetylase inhibitors (HDACi) increases immune signaling and recruits CD8(+) T cells and natural killer cells to fight ovarian carcinoma in murine models. This increased immune activity is caused by increased transcription of repetitive elements (RE) that form double-stranded RNA (dsRNA) and trigger an IFN response. To understand which REs are affected by epigenetic therapies in ovarian carcinoma, we assessed the effect of DNMTi and HDACi on ovarian carcinoma cell lines and patient samples. Subfamily- level (TEtranscripts) and individual locus- level (Telescope) analysis of REs showed that DNMTi treatment upregulated more REs than HDACi treatment. Upregulated REs were predominantly LTR and SINE subfamilies, and SINEs exhibited the greatest loss of DNA methylation upon DNMTi treatment. Cell lines with TP53 mutations exhibited significantly fewer upregulated REs with epigenetic therapy than wild-type TP53 cell lines. This observation was validated using isogenic cell lines; the TP53-mutant cell line had significantly higher baseline expression of REs but upregulated fewer upon epigenetic treatment. In addition, p53 activation increased expression of REs in wild-type but not mutant cell lines. These data give a comprehensive, genome-wide picture of RE chromatin and transcription-related changes in ovarian carcinoma after epigenetic treatment and implicate p53 in RE transcriptional regulation.
CRIS-Team WoS Importer:2021-11-05

Epigenetic therapy activates type I interferon signaling in murine ovarian cancer to reduce immunosuppression and tumor burden - Stone, Meredith L.; Chiappinelli, Katherine B.; Li, Huili; Murphy, Lauren M.; Travers, Meghan E.; Topper, Michael J.; Mathios, Dimitrios; Lim, Michael; Shih, Ie-Ming; Wang, Tian-Li; Hung, Chien-Fu; Bhargava, Vipul; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Ovarian cancer is the most lethal of all gynecological cancers, and there is an urgent unmet need to develop new therapies. Epithelial ovarian cancer (EOC) is characterized by an immune suppressive microenvironment, and response of ovarian cancers to immune therapies has thus far been disappointing. We now find, in a mouse model of EOC, that clinically relevant doses of DNA methyltransferase and histone deacetylase inhibitors (DNMTi and HDACi, respectively) reduce the immune suppressive microenvironment through type I IFN signaling and improve response to immune checkpoint therapy. These data indicate that the type I IFN response is required for effective in vivo antitumorigenic actions of the DNMTi 5-azacytidine (AZA). Through type I IFN signaling, AZA increases the numbers of CD45+ immune cells and the percentage of active CD8+ T and natural killer (NK) cells in the tumor microenvironment, while reducing tumor burden and extending survival. AZA also increases viral defense gene expression in both tumor and immune cells, and reduces the percentage of macrophages and myeloid-derived suppressor cells in the tumor microenvironment. The addition of an HDACi to AZA enhances the modulation of the immune microenvironment, specifically increasing T and NK cell activation and reducing macrophages over AZA treatment alone, while further increasing the survival of the mice. Finally, a triple combination of DNMTi/HDACi plus the immune checkpoint inhibitor α-PD-1 provides the best antitumor effect and longest overall survival, and may be an attractive candidate for future clinical trials in ovarian cancer.
EVALuna2:36339

Epigenetic Therapy Ties MYC Depletion to Reversing Immune Evasion and Treating Lung Cancer - Topper, Michael J.; Vaz, Michelle; Chiappinelli, Katherine B.; Shields, Christina E. Destefano; Niknafs, Noushin; Yen, Ray-Whay Chiu; Wenzel, Alyssa; Hicks, Jessica; Ballew, Matthew; Stone, Meredith; Tran, Phuoc T.; Zahnow, Cynthia A.; et al. (Cell, 2017)
Combining DNA-demethylating agents (DNA methyltransferase inhibitors [DNMTis]) with histone deacetylase inhibitors (HDACis) holds promise for enhancing cancer immune therapy. Herein, pharmacologic and isoform specificity of HDACis are investigated to guide their addition to a DNMTi, thus devising a new, low-dose, sequential regimen that imparts a robust anti-tumor effect for non-small-cell lung cancer (NSCLC). Using in-vitro-treated NSCLC cell lines, we elucidate an interferon α/β-based transcriptional program with accompanying upregulation of antigen presentation machinery, mediated in part through double-stranded RNA (dsRNA) induction. This is accompanied by suppression of MYC signaling and an increase in the T cell chemoattractant CCL5. Use of this combination treatment schema in mouse models of NSCLC reverses tumor immune evasion and modulates T cell exhaustion state towards memory and effector T cell phenotypes. Key correlative science metrics emerge for an upcoming clinical trial, testing enhancement of immune checkpoint therapy for NSCLC.
EVALuna2:36340

Evolution of PD-1 and PD-L1 Gene and Protein Expression in Primary Tumors and Corresponding Liver Metastases of Metastatic Bladder Cancer - Eckstein, Markus; Sikic, Danijel; Strissel, Pamela; Erlmeier, Franziska (European Urology, 2018)
EVALuna2:35883

Fiber alignment in 3D collagen networks as a biophysical marker for cell contractility - Böhringer, David; Bauer, Andreas; Moravec, Ivana; Bischof, Lars; Kah, Delf-Thorge Eric; Mark, Christoph; Grundy, Thomas J.; Görlach, Ekkehard; O'Neill, Geraldine M.; Budday, Silvia; Strissel, Pamela; Strick, Reiner; et al. (Matrix Biology, 2023)
Cells cultured in 3D fibrous biopolymer matrices exert traction forces on their environment that induce deformations and remodeling of the fiber network. By measuring these deformations, the traction forces can be reconstructed if the mechanical properties of the matrix and the force-free matrix configuration are known. These requirements limit the applicability of traction force reconstruction in practice. In this study, we test whether force-induced matrix remodeling can instead be used as a proxy for cellular traction forces. We measure the traction forces of hepatic stellate cells and different glioblastoma cell lines and quantify matrix remodeling by measuring the fiber orientation and fiber density around these cells. In agreement with simulated fiber networks, we demonstrate that changes in local fiber orientation and density are directly related to cell forces. By resolving Rho-kinase (ROCK) inhibitor-induced changes of traction forces, fiber alignment, and fiber density in hepatic stellate cells, we show that the method is suitable for drug screening assays. We conclude that differences in local fiber orientation and density, which are easily measurable, can be used as a qualitative proxy for changes in traction forces. The method is available as an open-source Python package with a graphical user interface.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Biopolymer Networks; Fiber Orientation; Mechanobiology; Traction Force Microscopy

Frequency of microsatellite instability (MSI) in upper tract urothelial carcinoma: comparison of the Bethesda panel and the Idylla MSI assay in a consecutively collected, multi-institutional cohort - Kullmann, Friederike; Strissel, Pamela; Strick, Reiner; Stöhr, Robert; Eckstein, Markus; Bertz, Simone; Wullich, Bernd; Sikic, Danijel; Wach, Sven; Taubert, Helge; Olbert, Peter; Heers, Hendrik; et al. (Journal of Clinical Pathology, 2021)
Aims Upper tract urothelial carcinoma (UTUC) is a rare malignancy with a poor prognosis which occurs sporadically or in few cases results from a genetic disorder called Lynch syndrome. Recently, examination of microsatellite instability (MSI) has gained importance as a biomarker: MSI tumours are associated with a better response to immunomodulative therapies. Limited data are known about the prevalence of MSI in UTUC. New detection methods using the fully automated Idylla MSI Assay facilitate analysis of increased patient numbers. Methods We investigated the frequency of MSI in a multi-institutional cohort of 243 consecutively collected UTUC samples using standard methodology (Bethesda panel), along with immunohistochemistry of mismatch repair (MMR) proteins. The same tumour cohort was retested using the Idylla MSI Assay by Biocartis. Results Using standard methodology, 230/243 tumours were detected as microsatellite stable (MSS), 4/243 tumours as MSI and 9/243 samples as invalid. In comparison, the Idylla MSI Assay identified four additional tumours as MSS, equalling 234/243 tumours; 4/243 were classified as MSI and only 5/243 cases as invalid. At the immunohistochemical level, MSI results were supported in all available cases with a loss in MMR proteins. The overall concordance between the standard and the Idylla MSI Assay was 98.35%. Time to result differed between 3 hours for Idylla MSI Assay and 2 days with the standard methodology. Conclusion Our data indicate a low incidence rate of MSI tumours in patients with UTUC. Furthermore, our findings highlight that Idylla MSI Assay can be applied as an alternative method of MSI analysis for UTUC.
CRIS-Team WoS Importer:2021-12-10

Gene expression and epigenetic aberrations in F1-placentas fathered by obese males - Mitchell, Megan; Strick, Reiner; Strissel, Pamela; Dittrich, Ralf; Mcpherson, Nicole O.; Lane, Michelle; Pliushch, Galyna; Potabattula, Ramya; Haaf, Thomas; El Hajj, Nady (Molecular Reproduction and Development, 2017)
Gene expression and/or epigenetic deregulation may have consequences for sperm and blastocysts, as well as for the placenta, together potentially contributing to problems observed in offspring. We previously demonstrated specific perturbations of fertilization, blastocyst formation, implantation, as well as aberrant glucose metabolism and adiposity in offspring using a mouse model of paternal obesity. The current investigation analyzed gene expression and methylation of specific CpG residues in F1 placentas of pregnancies fathered by obese and normal-weight male mice, using real-time PCR and bisulfite pyrosequencing. Our aim was to determine if paternal obesity deregulated placental gene expression and DNA methylation when compared to normal-weight males. Gene methylation of sperm DNA was analyzed and compared to placentas to address epigenetic transmission. Of the 10 paternally expressed genes (Pegs), 11 genes important for development and transport of nutrients, and the long-terminal repeat Intracisternal A particle (IAP) elements, derived from a member of the class II endogenous retroviral gene family, we observed a significant effect of paternal diet-induced obesity on deregulated expression of Peg3, Peg9, Peg10, and the nutrient transporter gene Slc38a2, and aberrant DNA methylation of the Peg9 promoter in F1 placental tissue. Epigenetic changes in Peg9 were also found in sperm from obese fathers. We therefore propose that paternal obesity renders changes in gene expression and/or methylation throughout the placental genome, which could contribute to the reproductive problems related to fertility and to the metabolic, long-term health impact on offspring.
EVALuna2:36349

Heterogeneity-analysis of molecular subtypes of muscle-invasive bladder cancer and their precursor lesions in multiregion mapped whole-organ bladders - Weyerer, Veronika; Lange, Fabienne; Wullweber, Adrian; Stöhr, Robert; Bertz, Simone; Wach, S.; Taubert, Helge; Wullich, Bernd; Sikic, Danijel; Strissel, Pamela; Strick, Reiner; Hartmann, Arndt; et al. (UROLOGIC ONCOLOGY-SEMINARS AND ORIGINAL INVESTIGATIONS, 2020)
CRIS-Team WoS Importer:2021-01-15

HLA-G expression associates with immune evasion muscle-invasive urothelial cancer and drives prognostic relevance - Branz, Annalena; Matek, Christian; Lange, Fabienne; Bahlinger, Veronika; Klümper, Niklas; Hölzel, Michael; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Wach, Sven; Taubert, Helge; Wullich, Bernd; et al. (Frontiers in Immunology, 2024)
Introduction: Urothelial bladder cancer is frequent and exhibits diverse prognoses influenced by molecular subtypes, urothelial subtype histology, and immune microenvironments. HLA-G, known for immune regulation, displays significant membranous expression in tumor tissues. Methods: We studied the protein expression of Human Leucocyte Antigen G (HLA-G) in 241 Muscle-Invasive Bladder Cancer (MIBC) patients, elucidating its potential clinical and biological significance. Protein expression levels were evaluated and correlated with molecular subtypes, histological characteristics, immune microenvironment markers, and survival outcomes. Results: High HLA-G expression associates with poor overall survival (OS) and diseasespecific survival (DSS), independent of clinicopathological parameters. HLA-G expression varies among molecular subtypes and Urothelial Subtype Histology, e.g., elevated expression levels in basal/squamous MIBC and those with sarcomatoid differentiation. Notably, HLA-G is increased in MIBC with an immune evasive microenvironment (high PD-L1 tumor cell expression, NK cell depletion, granzyme B (GZMB)/CD8 ratio reduction, MHC class I (MHCI) expression reduction) that are characterized by immunosuppressive features and poor prognosis. Furthermore, HLA-G correlates with elevated levels of other immune checkpoint proteins (TIGIT, LAG3, CTLA-4), indicating its role in immune evasion. Discussion: Our findings underscore HLA-G’s role as a potential prognostic marker and interesting immunotherapeutic target in MIBC. Its impact on immune evasion mechanisms and broad expression, coupled with associations withpoor survival and distinct tumor phenotypes, positions HLA-G as a promising protein for further exploration in developing targeted immunotherapies for MIBC patients.
CRIS-Team Scopus Importer:2024-11-15
Keywords: HLA-G; immune checkpoints; immune evasion; immune microenvironment; urothelial cancer

Human endogenous retroviruses differentially regulate immune checkpoints and modulation of immune responses in serous ovarian carcinoma - Strissel, Pamela; Chiappinelli, Katherine B.; Strehl, Johanna; Wuefel, Franziska M. B.; Beckmann, Matthias; Baylin, Stephen B.; Strick, Reiner (2017)
EVALuna2:34862

Hyperandrogenemia and high prolactin in congenital utero-vaginal aplasia patients - Oppelt, Patricia; Mueller, Andreas; Stephan, Liana; Dittrich, Ralf; Lermann, Johannes; Büttner, Christian; Ekici, Arif Bülent; Conzelmann, Gabi; Seeger, Harald; Schoeller, Dorit; Rall, Katharina; Beckmann, Matthias; et al. (Reproduction, 2017)
Patients with the Mayer-Rokitansky-Küster-Hauser syndrome (MRKH) have a congenital utero-vaginal cervical aplasia, but normal or hypoplastic adnexa and develop with normal female phenotype. Some reports mostly demonstrated regular steroid hormone levels in small MRKH cohorts including single MRKH patients with hyperandrogenemia and a clinical presentationof hirsutism and acne has also been shown. Genetically a correlation of WNT4 mutations with singular MRKH patients and hyperandrogenemia was noted. This study analyzed the hormone status of 215 MRKH patients by determining the levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), estradiol, 17-OH progesterone, testosterone, dehydroepiandrosterone sulfate (DHEAS), sex hormone-binding globulin (SHBG) and prolactin to determine the incidence of hyperandrogenemia and hyperprolactinemia in MRKH patients. Additional calculations and a ratio of free androgen index and biologically active testosterone revealed a hyperandrogenemia rate of 48.3%, hyperprolactinemia of 9.8% and combined hyperandrogenemia and hyperprolactinemia of 4.2% in MRKH patients. The rates of hirsutism, acne and especially polycystic ovary syndrome (PCOS) were in the normal range of the population and showed no correlation with hyperandrogenemia. A weekly hormone assessment over 30 days comparing 5 controls and 7 MRKH patients revealed high androgen and prolactin, but lower LH/FSH and SHBG levels with MRKH patients. The sequencing of WNT4, WNT5A, WNT7A and WNT9B demonstrated no significant mutations correlating with hyperandrogenemia. Taken together, this study shows that over 52% of MRKH patients have hyperandrogenemia without clinical presentation and 14% hyperprolactinemia, which appeals for general hormone assessment and adjustments of MRKH patients.
EVALuna2:9378

Hypermethylation and loss of retinoic acid receptor responder 1 expression in human choriocarcinoma - Hübner, Hanna; Strick, Reiner; Wachter, David Lukas; Kehl, Sven; Strissel, Pamela; Schneider-Stock, Regine; Rascher, Wolfgang; Horn, L. C.; Beckmann, Matthias; Rübner, Matthias; Fahlbusch, F. B.; Hartner, Andrea (Journal of Experimental & Clinical Cancer Research, 2017)
BACKGROUND: Human placental development resembles tumorigenesis, due to the invasive and fusogenic potential of trophoblasts. However, these features are tightly controlled in trophoblasts. Disturbance of this spatial and temporal regulation is thought to contribute to the rare formation of choriocarcinomas. Promoter hypermethylation and loss of the tumor suppressor Retinoic acid receptor responder 1 (RARRES1) were shown to contribute to cancer progression. Our study investigated the epigenetic and transcriptional regulation of RARRES1 in healthy human placenta in comparison to choriocarcinoma cell lines and cases. METHODS: Three choriocarcinoma cell lines (Jeg-3, JAR and BeWo) were treated with three different retinoic acid derivates (Am580, Tazarotene and all-trans retinoic acid) and 5-aza-2'-deoxycytidine. We analyzed RARRES1 promoter methylation by pyrosequencing and performed realtime-PCR quantification to determine RARRES1 expression in placental tissue and trophoblastic cell lines. Additionally, RARRES1 was stained in healthy placentas and in biopsies of choriocarcinoma cases (n = 10) as well as the first trimester trophoblast cell line Swan71 by immunofluorescence and immunohistochemistry. RESULTS: In the choriocarcinoma cell lines, RARRES1 expression could not be induced by sole retinoic acid treatment. Stimulation with 5-aza-2'-deoxycytidine significantly induced RARRES1 expression, which then could be further increased with Am580, Tazarotene and all-trans retinoic acid. In comparison to healthy placenta, choriocarcinoma cell lines showed a hypermethylation of the RARRES1 promoter, which correlated with a reduced RARRES1 expression. In concordance, RARRES1 protein expression was lost in choriocarcinoma tissue. Additionally, in the trophoblastic cell line Swan71, we found a significant induction of RARRES1 expression with increased cell density, during mitosis and in syncytial knots. CONCLUSIONS: Our findings showed that RARRES1 expression is absent in choriocarcinoma due to promoter methylation. Based on our analysis, we hypothesize that RARRES1 might exert tumor suppressive functions in multiple cellular processes (e.g. cell cycle regulation, adhesion, invasion and apoptosis).
EVALuna2:33950

Immune Cell Gene Expression Signature is Associated with Improved Outcome in Muscle-Invasive Urothelial Bladder Cancer Patients Treated with Radical Cystectomy - Eckstein, Markus; Strissel, Pamela; Strick, Reiner; Weyerer, Veronika; Wirtz, Ralph M.; Pfannstiel, Carolin; Wullweber, Adrian; Lange, Fabienne; Erben, Philipp; Stöhr, Robert; Bertz, Simone; Geppert, Carol-Immanuel; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

IMPAIRED GENE-EXPRESSION AND EPIGENETIC REGULATION OF RETINOIC ACID RECEPTOR RESPONDER 1 IN PREECLAMPSIA AND CHORIOCARCINOMA - Hübner, Hanna; Fahlbusch, Fabian B.; Strissel, Pamela; Strick, Reiner; Wachter, David; Beckmann, Matthias; Rübner, Matthias (2016)
EVALuna2:32961

Improved Bladder Tumor RNA Isolation from Archived Tissues Using Methylene Blue for Normalization, Multiplex RNA Hybridization, Sequencing and Subtyping - Köhler, Stefanie; Brandl, Lisa; Strissel, Pamela; Glossner, Laura; Ekici, Arif Bülent; Angeloni, Miriam; Ferrazzi, Fulvia; Bahlinger, Veronika; Hartmann, Arndt; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner (International Journal of Molecular Sciences, 2022)
Methylene blue (MB) is a dye used for histology with clinical importance and intercalates into nucleic acids. After MB staining of formalin fixed paraffin embedded (FFPE) muscle invasive bladder cancer (MIBC) and normal urothelium, specific regions could be microdissected. It is not known if MB influences RNA used for gene expression studies. Therefore, we analyzed MIBC using five different RNA isolation methods comparing patient matched FFPE and fresh frozen (FF) tissues pre-stained with or without MB. We demonstrate a positive impact of MB on RNA integrity with FF tissues using real time PCR with no interference of its chemical properties. FFPE tissues showed no improvement of RNA integrity, which we propose is due to formalin induced nucleotide crosslinks. Using direct multiplex RNA hybridization the best genes for normalization of MIBC and control tissues were identified from 34 reference genes. In addition, 5SrRNA and 5.8SrRNA were distinctive reference genes detecting <200 bp fragments important for mRNA analyses. Using these normalized RNAs from MB stained MIBC and applying multiplex RNA hybridization and mRNA sequencing, a minimal gene expression panel precisely identified luminal and basal MIBC tumor subtypes, important for diagnosis, prognosis and chemotherapy response.
CRIS-Team WoS Importer:2022-09-30

Inhibiting DNA Methylation Causes an Interferon Response in Cancer via dsRNA Including Endogenous Retroviruses - Chiappinelli, Katherine B.; Strissel, Pamela; Desrichard, Alexis; Li, Huili; Henke, Christine; Akman, Benjamin; Hein, Alexander; Rote, Neal S.; Cope, Leslie M.; Snyder, Alexandra; Makarov, Vladimir; Buhu, Sadna; et al. (Cell, 2015)
We show that DNA methyltransferase inhibitors (DNMTis) upregulate immune signaling in cancer through the viral defense pathway. In ovarian cancer (OC), DNMTis trigger cytosolic sensing of double-stranded RNA (dsRNA) causing a type I interferon response and apoptosis. Knocking down dsRNA sensors TLR3 and MAVS reduces this response 2-fold and blocking interferon beta or its receptor abrogates it. Upregulation of hypermethylated endogenous retrovirus (ERV) genes accompanies the response and ERV overexpression activates the response. Basal levels of ERV and viral defense gene expression significantly correlate in primary OC and the latter signature separates primary samples for multiple tumor types from The Cancer Genome Atlas into low versus high expression groups. In melanoma patients treated with an immune checkpoint therapy, high viral defense signature expression in tumors significantly associates with durable clinical response and DNMTi treatment sensitizes to anti-CTLA4 therapy in a pre-clinical melanoma model.
EVALuna2:17550

Inhibition of adhesion, proliferation, and invasion of primary endometriosis and endometrial stromal and ovarian carcinoma cells by a nonhyaluronan adhesion barrier gel - Renner, Stefan; Strissel, Pamela; Beckmann, Matthias; Lermann, Johannes; Burghaus, Stefanie; Hackl, Janina; Fasching, Peter; Strick, Reiner (BioMed Research International, 2015)
Endometriosis is a chronic disease of women in the reproductive age, defined as endometrial cells growing outside of the uterine cavity and associated with relapses. Relapses are hypothesized to correlate with incomplete surgical excision or result from nonrandom implantation of new endometrial implants in adjacent peritoneum. Thus, surgical excision could lead to free endometriotic cells or tissue residues, which readhere, grow, and invade into recurrent lesions. Barrier agents are frequently used to prevent postoperative adhesions. We tested if the absorbable cell adhesion barrier gel Intercoat consisting of polyethylene oxide and sodium carboxymethyl cellulose could inhibit cellular adhesion, proliferation, and invasion of primary endometriosis and endometrial cells. Due to an association of endometriosis with ovarian carcinoma, we tested two ovarian carcinoma cell lines. Prior to cell seeding, a drop of the barrier gel was placed in cell culture wells in order to test inhibition of adherence and proliferation or coated over a polymerized collagen gel to assay for prevention of invasion. Results showed that the barrier gel significantly inhibited cell adherence, proliferation, and invasion of endometriosis and endometrial stromal cells as well as ovarian carcinoma cells in culture. Our findings could help to prevent local cell growth/invasion and possible consequent recurrences.
EVALuna2:17548

Integration of spatial pd-l1 expression with the tumor immune microenvironment outperforms standard pd-l1 scoring in outcome prediction of urothelial cancer patients - Weyerer, Veronika; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Geppert, Carol-Immanuel; Bertz, Simone; Lange, Fabienne; Taubert, Helge; Wach, Sven; Breyer, Johannes; Bolenz, Christian; Erben, Philipp; et al. (Cancers, 2021)
Background: Immune therapy has gained significant importance in managing urothelial cancer. The value of PD-L1 remains a matter of controversy, thus requiring an in-depth analysis of its biological and clinical relevance. Methods: A total of 193 tumors of muscle-invasive bladder cancer patients (MIBC) were assessed with four PD-L1 assays. PD-L1 scoring results were correlated with data from a comprehensive digital-spatial immune-profiling panel using descriptive statistics, hierarchical clustering and uni-/multivariable survival analyses. Results: PD-L1 scoring algorithms are heterogeneous (agreements from 63.1% to 87.7%), and stems from different constellations of immune and tumor cells (IC/TC). While Ventana IC5% algorithm identifies tumors with high inflammation and favorable baseline prognosis, CPS10 and the TCarea25%/ICarea25% algorithm identify tumors with TC and IC expression. Spatially organized immune phenotypes, which correlate either with high PD-L1 IC expression and favorable prognosis or constitutive PD-L1 TC expression and poor baseline prognosis, cannot be resolved properly by PD-L1 algorithms. PD-L1 negative tumors with relevant immune infiltration can be detected by sTILs scoring on HE slides and digital CD8+ scoring. Conclusions: Contemporary PD-L1 scoring algorithms are not sufficient to resolve spatially distributed MIBC immune phenotypes and their clinical implications. A more comprehensive view of immune phenotypes along with the integration of spatial PD-L1 expression on IC and TC is necessary in order to stratify patients for ICI.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Bladder cancer; Immune phenotypes; PD-1; PD-L1; TILs; Urothelial cancer

Long-Term Endurance Exercise in Humans Stimulates Cell Fusion of Myoblasts along with Fusogenic Endogenous Retroviral Genes In Vivo - Frese, Sebastian; Rübner, Matthias; Suhr, Frank; Konou, Thierry M.; Tappe, Kim A.; Toigo, Marco; Jung, Hans H.; Henke, Christine; Steigleder, Ruth; Strissel, Pamela; Hübner, Hanna; Beckmann, Matthias; et al. (PLoS ONE, 2015)
Myogenesis is defined as growth, differentiation and repair of muscles where cell fusion of myoblasts to multinucleated myofibers is one major characteristic. Other cell fusion events in humans are found with bone resorbing osteoclasts and placental syncytiotrophoblasts. No unifying gene regulation for natural cell fusions has been found. We analyzed skeletal muscle biopsies of competitive cyclists for muscle-specific attributes and expression of human endogenous retrovirus (ERV) envelope genes due to their involvement in cell fusion of osteoclasts and syncytiotrophoblasts. Comparing muscle biopsies from post- with the pre-competitive seasons a significant 2.25-fold increase of myonuclei/mm fiber, a 2.38-fold decrease of fiber area/nucleus and a 3.1-fold decrease of satellite cells (SCs) occurred. We propose that during the pre-competitive season SC proliferation occurred following with increased cell fusion during the competitive season. Expression of twenty-two envelope genes of muscle biopsies demonstrated a significant increase of putative muscle-cell fusogenic genes Syncytin-1 and Syncytin-3, but also for the non-fusogenic erv3. Immunohistochemistry analyses showed that Syncytin-1 mainly localized to the sarcolemma of myofibers positive for myosin heavy-chain isotypes. Cellular receptors SLC1A4 and SLC1A5 of Syncytin-1 showed significant decrease of expression in post-competitive muscles compared with the pre-competitive season, but only SLC1A4 protein expression localized throughout the myofiber. Erv3 protein was strongly expressed throughout the myofiber, whereas envK1-7 localized to SC nuclei and myonuclei. Syncytin-1 transcription factors, PPAR? and RXR?, showed no protein expression in the myofiber, whereas the pCREB-Ser133 activator of Syncytin-1 was enriched to SC nuclei and myonuclei. Syncytin-1, Syncytin-3, SLC1A4 and PAX7 gene regulations along with MyoD1 and myogenin were verified during proliferating or actively-fusing human primary myoblast cell cultures, resembling muscle biopsies of cyclists. Myoblast treatment with anti-Synycytin-1 abrogated cell fusion in vitro. Our findings support functional roles for ERV envelope proteins, especially Syncytin-1, contributing to cell fusion of myotubes.
EVALuna2:17549

Melt Electrowritten In Vitro Radial Device to Study Cell Growth and Migration - Bakirci, Ezgi; Schaefer, Natascha; Dahri, Ouafa; Hrynevich, Andrei; Strissel, Pamela; Strick, Reiner; Dalton, Paul D.; Villmann, Carmen (Advanced Biosystems, 2020)
The development of in vitro assays for 3D microenvironments is essential for understanding cell migration processes. A 3D-printed in vitro competitive radial device is developed to identify preferred Matrigel concentration for glioblastoma migration. Melt electrowriting (MEW) is used to fabricate the structural device with defined and intricate radial structures that are filled with Matrigel. Controlling the printing path is necessary to account for the distance lag in the molten jet, the applied electric field, and the continuous direct-writing nature of MEW. Circular printing below a diameter threshold results in substantial inward tilting of the MEW fiber wall. An eight-chamber radial device with a diameter of 9.4 mm is printed. Four different concentrations of Matrigel are dispensed into the radial chambers. Glioblastoma cells are seeded into the center and grow into all chambers within 8 days. The cell spreading area demonstrates that 6 and 8 mg mL−1 of Matrigel are preferred over 2 and 4 mg mL−1. Furthermore, topographical cues via the MEW fiber wall are observed to promote migration even further away from the cell seeding depot. Previous studies implement MEW to fabricate cell invasive scaffolds whereas here it is applied to 3D-print in vitro tools to study cell migration.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 3D cell culture; biofabrication; electrohydrodynamic; melt electrospinning writing

Migration in Confined 3D Environments Is Determined by a Combination of Adhesiveness, Nuclear Volume, Contractility, and Cell Stiffness - Lautscham, Lena; Kaemmerer, Christoph; Lange, Janina; Kolb, Thorsten; Mark, Christoph; Schilling, Achim; Strissel, Pamela; Strick, Reiner; Gluth, Caroline Laura Maria; Rowat, Amy C.; Metzner, Claus; Fabry, Ben (Biophysical Journal, 2015)
In cancer metastasis and other physiological processes, cells migrate through the three-dimensional (3D) extracellular matrix of connective tissue and must overcome the steric hindrance posed by pores that are smaller than the cells. It is currently assumed that low cell stiffness promotes cell migration through confined spaces, but other factors such as adhesion and traction forces may be equally important. To study 3D migration under confinement in a stiff (1.77 MPa) environment, we use soft lithography to fabricate polydimethylsiloxane (PDMS) devices consisting of linear channel segments with 20 ?m length, 3.7 ?m height, and a decreasing width from 11.2 to 1.7 ?m. To study 3D migration in a soft (550 Pa) environment, we use self-assembled collagen networks with an average pore size of 3 ?m. We then measure the ability of four different cancer cell lines to migrate through these 3D matrices, and correlate the results with cell physical properties including contractility, adhesiveness, cell stiffness, and nuclear volume. Furthermore, we alter cell adhesion by coating the channel walls with different amounts of adhesion proteins, and we increase cell stiffness by overexpression of the nuclear envelope protein lamin A. Although all cell lines are able to migrate through the smallest 1.7 ?m channels, we find significant differences in the migration velocity. Cell migration is impeded in cell lines with larger nuclei, lower adhesiveness, and to a lesser degree also in cells with lower contractility and higher stiffness. Our data show that the ability to overcome the steric hindrance of the matrix cannot be attributed to a single cell property but instead arises from a combination of adhesiveness, nuclear volume, contractility, and cell stiffness.
EVALuna2:17547

Nanoscale bioactive glass activates osteoclastic differentiation of RAW 264.7 cells - Detsch, Rainer; Rübner, Matthias; Strissel, Pamela; Mohn, Dirk; Strasser, Erwin; Stark, Wendelin J.; Strick, Reiner; Boccaccini, Aldo R. (Nanomedicine, 2016)
There is limited knowledge regarding differentiation of osteoclasts in the presence of nanoscale bioactive glass (nBG). This investigation examined increasing concentrations of 45S5 nBG and their influence on osteoclast differentiation.Different concentrations of 45S5 nBG were cultured up to 14 days with the murine RAW264.7 cell line and human primary monocytes cultured with M-CSF and RANKL.Culturing cells for 14 days with 500 ?g/ml nBG showed a viability of 100%; however DNA synthesis was reduced, supporting differentiation into osteoclast-like cells. Using RAW cells, activation of nine genes, including cell fusion genes, occurred in an nBG concentration dependent manner. Low concentrations of nBG increased expression of genes involved in commitment to cell fusion, whereas high concentrations increased gene expression supporting osteoclast-like differentiation.nBG enhances both RAW264.7 and human osteoclast differentiation. nBG controlled gene expression in a concentration dependent manner could reflect normal regulation during bone growth.
EVALuna2:15997

Plasticity of patient-matched normal mammary epithelial cells is dependent on autologous adipose-derived stem cells - Kengelbach-Weigand, Annika; Tasbihi, Kereshmeh; Strissel, Pamela; Schmid, Rafael; Marques, Jasmin Monteiro; Beier, Justus; Beckmann, Matthias; Strick, Reiner; Horch, Raymund E.; Boos, Anja (Scientific Reports, 2019)
Due to the increasing clinical application of adipose-derived stem cells (ADSC), e.g. lipotransfer for breast reconstruction, this study aimed to gain novel insights regarding ADSC influence on breast tissue remodeling and determine patient-dependent factors affecting lipotransfer as well as begin to address its oncological risks. The ADSC secretome was analyzed from five normal breast reduction patients and contained elevated levels of growth factors, cytokines and proteins mediating invasion. ADSC/ADSC secretomes were tested for their influence on the function of primary mammary epithelial cells, and tumor epithelial cells using cell culture assays. ADSC/ADSC secretomes significantly stimulated proliferation, transmigration and 3D-invasion of primary normal and tumor epithelial cells. IL-6 significantly induced an EMT and invasion. The ADSC secretome significantly upregulated normal epithelial cell gene expression including MMPs and ECM receptors. Our study supports that ADSC and its secretome promote favorable conditions for normal breast tissue remodeling by changing the microenvironment. and may also be important regarding residual breast cancer cells following surgery.
CRIS-Team Scopus Importer:2019-08-06

Regulation of murine placentogenesis by the retroviral genes Syncytin-A, Syncytin-B and Peg10 - Henke, Christine; Ruebner, Matthias; Faschingbauer, Florian; Stolt, Claus; Schäfer, Natascha; Lang, Nadine; Beckmann, Matthias; Strissel, Pamela; Strick, Reiner (Differentiation, 2013)
The murine placenta has a trichorial structure with two multinucleated syncytiotrophoblast (SCT) layers representing a barrier between the maternal and fetal blood system. Genes of endogenous retroviruses and retrotransposon-derived paternally expressed genes (Peg), remnants of past infections and integrations in the genome, have essential functions in placentogenesis. Previous studies showed that the envelope genes Syncytin-A and Syncytin-B were essential for cell-cell fusion of the SCT. The goal of this study was to analyze the temporal localization and expression of nine genes throughout placental development from embryonic day (E)8.5 to E18.5 using in situ-hybridization and absolute RNA-quantification. These included a comparison of previously characterized genes from the labyrinth Syncytin-A, Syncytin-B, Gcm1, the junctional zone PL-1, PL-2, Plf, Tpbpa with two further characterized genes Peg10 and Tpbpb. Syncytin-A and Syncytin-B RNA localized to SCT-I and SCT-II, respectively. Peg10 RNA localized to all extraembryonic tissues, specifically to the parietal and sinusoidal TGC of the labyrinth layer, which is in contact with SCT-I and the maternal blood. All three retroviral/retrotransposon-derived genes showed the highest expression at E16.5, but Peg10 with 188,917.1 molecules/ng cDNA was 208-fold and 106.8-fold higher expressed than Syncytin-A and Syncytin-B, respectively. Tpbpb localized to the junctional zone and showed the highest expression at E16.5 along with PL-2, Plf, Tpbpa, but not PL-1, which decreased in expression at E10.5. To investigate a role of Syncytin-A, Syncytin-B and Peg10 in cell-cell fusion, we established a cell culture system with fractionated primary trophoblasts from murine placentae. Culturing trophoblasts for up to 72h partly resembled trophoblast development in vivo according to the nine marker genes. Knockdown of Syncytin-A demonstrated a functional regulation of cell-cell fusion, where knockdown of Peg10 showed no involvement in cell fusion. Due to the expression of Peg10 in TGCs, we propose an essential functional role in the fetal-maternal blood system.
EVALuna2:4934

Reply to Haffner et al.: DNA hypomethylation renders tumors more immunogenic - Stone, Meredith L.; Chiappinelli, Katherine B.; Li, Huili; Murphy, Lauren M.; Travers, Meghan E.; Topper, Michael J.; Mathios, Dimitrios; Lim, Michael; Shih, Le-Ming; Wang, Tian-Li; Hung, Chien-Fu; Bhargava, Vipul; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
EVALuna2:210063

Role of Fiber Thickness and Surface Treatment of Electrospun Polycaprolactone Matrices on the Growth of Different Breast Cancer‐Associated Cells - Sivakumar, Sankaranarayanan; Schmid, Rafael; Wieland, Annalena; Strissel, Pamela; Strick, Reiner; Fischer, Lena; Thievessen, Ingo; Kataev, Elmar; Arkudas, Andreas; Horch, Raymund E.; Schubert, Dirk W.; Kengelbach-Weigand, Annika (Advanced Materials Interfaces, 2022)
Cancer models mimicking the tumor microenvironment are necessary to successfully develop and predict responses of oncological drugs. In this study, electrospun polycaprolactone (PCL) matrices are tested for the development of an in vitro breast cancer model. The effects of fiber thickness and plasma-treatment of the matrices on in vitro growth of breast cancer-associated cells, namely breast cancer cells MDA-MB-231, primary adipose-derived stem cells (ADSCs) and primary endothelial progenitor cells (EPCs) are evaluated. Surface treatment of the matrices by air-plasma leads to increased oxygen/carbon ratio and hydrophilicity. WST-8 analysis reveals that the proliferation of all three cell types increased exponentially over 12 d on all matrices. MDA-MB-231 and ADSC show a higher proliferation on nanofibers due to enhanced cellular adhesion compared to microfibers. In contrast, EPCs show a significantly higher proliferation on microfibers than on nanofibers at day 12 which can further be significantly improved by air-plasma treatment. Cross-sectioning analysis shows that cells grow on the surface of nanofibers, while microfibers have considerable cellular infiltration. These findings suggest that the electrospun PCL matrices are a suitable tool for the development of breast cancer models containing several cell types, which can ultimately lead to designing novel tumor therapies.<br

Selective expression of sense and antisense transcripts of the sushi-ichi-related retrotransposon - derived family during mouse placentogenesis - Henke, Christine; Strissel, Pamela; Schubert, Maria-Theresa; Mitchell, Megan; Stolt, Claus; Faschingbauer, Florian; Beckmann, Matthias; Strick, Reiner (Retrovirology, 2015)
LTR-retrotransposons became functional neogenes through evolution by acquiring promoter sequences, regulatory elements and sequence modification. Mammalian retrotransposon transcripts (Mart1-9), also called sushi-ichi-related retrotransposon-homolog (SIRH) genes, are a class of Ty3/gypsy LTR-retroelements showing moderate homology to the sushi-ichi LTR-retrotransposon in pufferfish. Rtl1/Mart1 and Peg10/Mart2 expression in mouse placenta and demonstration of their functional roles during placental development exemplifies their importance in cellular processes. In this study, we analyzed all eleven mouse Mart genes from the blastocyst stage and throughout placentogenesis in order to gain information about their expression and regulation.Quantitative PCR, in situ hybridization (ISH) and immunoblotting showed various expression patterns of the 11 mouse Mart genes through different placental stages. Zcchc5/Mart3, Zcchc16/ Mart4 and Rgag1/Mart9 expression was undetectable. Rtl1/Mart1, Peg10/Mart2, Rgag4/Mart5 - Cxx1a,b,c/Mart8b,c,a gene expression was very low at the blastocyst stage. Later placental stages showed an increase of expression for Rtl1/Mart1, Rgag4/Mart5 - Cxx1a,b,c/Mart8b,c,a, the latter up to 1,489 molecules/ng cDNA at E9.5. From our recently published findings Peg10/Mart2 was the most highly expressed Mart gene. ISH demonstrated sense and antisense transcript co-localization of Rgag4/Mart5 to Cxx1a,b,c/Mart8b,c,a in trophoblast subtypes at the junctional zone, with an accumulation of antisense transcripts in the nuclei. To validate these results, we developed a TAG-aided sense/antisense transcript detection (TASA-TD) method, which verified sense and antisense transcripts for Rtl1/Mart1, Rgag4/Mart5 - Cxx1a,b,c/Mart8b,c,a. Except for Rtl1/Mart1 and Cxx1a,b/Mart8b,c all other Mart genes showed a reduced amount of antisense transcripts. Northern blot and 5' and 3' RACE confirmed both sense and antisense transcripts for Ldoc1/Mart7 and Cxx1a,b,c/Mart8b,c,a. Immunoblotting demonstrated a single protein throughout all placental stages for Ldoc1/Mart7, but for Cxx1a,b,c/Mart8b,c,a a switch occurred from a 57 kDa protein at E10.5 and E14.5 to a 25 kDa protein at E16.5 and E18.5.RNA and protein detection of mouse Mart genes support neo-functionalization of retrotransposons in mammalian genomes. Undetectable expression of Zcchc5/Mart3, Zcchc16/Mart4 and Rgag1/Mart9 indicate no role during mouse placentogenesis. Rgag4/Mart5 to Cxx1a,b,c/Mart8b,c,a gene expression support a role for differentiation from the ectoplacental cone. Mart antisense transcripts and protein alterations predict unique and complex molecular regulation in a time directed manner throughout mouse placentogenesis.
EVALuna2:4979

Selective isolation and characterization of primary cells from normal breast and tumors reveal plasticity of adipose derived stem cells - Weigand, Annika; Boos, Anja; Tasbihi, Kereshmeh; Beier, Justus; Dalton, Paul D.; Schrauder, Michael; Horch, Raymund E.; Beckmann, Matthias; Strissel, Pamela; Strick, Reiner (Breast Cancer Research, 2016)
There is a need to establish more cell lines from breast tumors in contrast to immortalized cell lines from metastatic effusions in order to represent the primary tumor and not principally metastatic biology of breast cancer. This investigation describes the simultaneous isolation, characterization, growth and function of primary mammary epithelial cells (MEC), mesenchymal cells (MES) and adipose derived stem cells (ADSC) from four normal breasts, one inflammatory and one triple-negative ductal breast tumors.A total of 17 cell lines were established and gene expression was analyzed for MEC and MES (n = 42) and ADSC (n = 48) and MUC1, pan-KRT, CD90 and GATA-3 by immunofluorescence. DNA fingerprinting to track cell line identity was performed between original primary tissues and isolates. Functional studies included ADSC differentiation, tumor MES and MEC invasion co-cultured with ADSC-conditioned media (CM) and MES adhesion and growth on 3D-printed scaffolds.Comparative analysis showed higher gene expression of EPCAM, CD49f, CDH1 and KRTs for normal MEC lines; MES lines e.g. Vimentin, CD10, ACTA2 and MMP9; and ADSC lines e.g. CD105, CD90, CDH2 and CDH11. Compared to the mean of all four normal breast cell lines, both breast tumor cell lines demonstrated significantly lower ADSC marker gene expression, but higher expression of mesenchymal and invasion gene markers like SNAI1 and MMP2. When compared with four normal ADSC differentiated lineages, both tumor ADSC showed impaired osteogenic and chondrogenic but enhanced adipogenic differentiation and endothelial-like structures, possibly due to high PDGFRB and CD34. Addressing a functional role for overproduction of adipocytes, we initiated 3D-invasion studies including different cell types from the same patient. CM from ADSC differentiating into adipocytes induced tumor MEC 3D-invasion via EMT and amoeboid phenotypes. Normal MES breast cells adhered and proliferated on 3D-printed scaffolds containing 20 fibers, but not on 2.5D-printed scaffolds with single fiber layers, important for tissue engineering.Expression analyses confirmed successful simultaneous cell isolations of three different phenotypes from normal and tumor primary breast tissues. Our cell culture studies support that breast-tumor environment differentially regulates tumor ADSC plasticity as well as cell invasion and demonstrates applications for regenerative medicine.
EVALuna2:15613

Single nucleotide polymorphism D1853N of the ATM gene may alter the risk for breast cancer - Schrauder, M.; Frank, S.; Strissel, Pamela; Lux, Michael P.; Bani, Mayada; Rauh, C.; Sieber, Cornel; Heusinger, K.; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Strick, Reiner; Beckmann, Matthias; et al. (Journal of Cancer Research and Clinical Oncology, 2008)
Purpose Various ATM (ataxia telangiectasia-mutated) mutations and polymorphisms have been reported to be associated with an increased breast cancer risk. Recent studies have produced contradictory results regarding the association between ATM genetic variants and breast cancer risk.Materials and methods The common ATM polymorphism 5557G > A (p.D1853N) (rs1801516), previously suggested to be associated with bilateral breast cancer, was analyzed using real-time PCR in 514 unselected patients with breast cancer and 511 age-matched healthy control individuals. DNA was obtained from peripheral blood draw.Results The ATM genotype was weakly associated with the risk for breast cancer (P = 0.04 for the overall test). The odds ratio for women with a heterozygous genotype was 0.70 (95% CI, 0.52-0.94) and for the homozygous variant 0.63 (95% CI, 0.27-1.49). Disease-free survival and overall survival showed no significant association with specific genotypes.Conclusions The results of this study might suggest a minor association between polymorphism 5557G > A and a reduced risk of breast cancer.
Keywords: TM gene variants; polymorphism; breast cancer; DNA damage; epidemiology; association

Spatial Immunephenotypes of Distant Metastases but not Matched Primary Urothelial Carcinomas Predict Response to Immune Checkpoint Inhibition - Erlmeier, Franziska; Klümper, Niklas; Landgraf, Laura; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Taubert, Helge; Wach, Sven; Geppert, Carol-Immanuel; Bahlinger, Veronika; Breyer, Johannes; Ritter, Manuel; et al. (European Urology, 2022)
Background: The value of programmed cell death ligand-1 (PD-L1) to predict durable responses to immune checkpoint inhibitors (ICIs) in metastatic urothelial carcinoma (mUC) is inconsistent. We hypothesize that the use of archived primary tumor material (PRIM) for PD-L1 testing in clinical trials not properly reflecting the metastatic disease status (MET) contributes to this clinical issue. Objective: To analyze the predictive and prognostic value of PD-L1, spatial immunephenotypes, and major histocompatibility complex class I (MHC-I) determined in patient-matched PRIM/MET. Design, setting, and participants: PD-L1, spatial immunephenotypes, and MHC-I were examined in 154 mUC patients with at least one available pretreatment MET (138 patient-matched PRIM/MET pairs). Outcome measurements and statistical analysis: PD-L1, spatial immunephenotype, and MHC-I status of (patient-matched PRIM and) pretreatment MET were correlated with chemotherapy and ICI response and outcomes. Results and limitations: Discordance rates in patient-matched PRIM/MET were 25/30%, 36%, and 49% for PD-L1 (CPS10/IC5%), immunephenotypes, and MHC-I (loss vs preserved), respectively. Correlations with chemotherapy and ICI responses were observed for immunephenotypes and MHC-I status determined in MET (not for PD-L1 alone), but not in PRIM. In case of ICIs, patients with cytotoxic tumor immune microenvironment (TIME) showed durable responses with disease control rates of 90% and a hazard ratio for disease progression/death of 0.05 (95% confidence interval: 0.01–0.65) versus patients with immunedepleted MET (disease control rate 29%). MET MHC-I status added an incremental value to predict durable ICI responses. Limitations include the partly retrospective design and the lack of MET multisampling on individual patient level. Conclusions: The TIME is subject to substantial dynamics during metastatic evolution. MET immunephenotypes and MHC-I statuses show promising potential to predict chemotherapy and durable ICI responses, while the PRIM TIME does not. Thus, future clinical trials should rather rely on pretreatment MET biopsies reflecting the current immunological disease state than on PRIM. Patient summary: Prediction of chemotherapy and responses to immune checkpoint inhibitors might be possible using representative pretreatment metastatic biopsies.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Immune microenvironment; Immune therapy; Metastatic urothelial cancer; Subtypes; Urothelial cancer

Tert promoter mutation analysis of whole-organ mapping bladder cancers - Weyerer, Veronika; Eckstein, Markus; Strissel, Pamela; Wullweber, Adrian; Lange, Fabienne; Tögel, Lars; Geppert, Carol-Immanuel; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; et al. (Genes, 2021)
Background: Multifocal occurrence is a main characteristic of urothelial bladder cancer (UBC). Whether urothelial transformation is caused by monoclonal events within the urothelium, or by polyclonal unrelated events resulting in several tumor clones is still under debate. TERT promoter mutations are the most common somatic alteration identified in UBC. In this study, we analyzed different histological tissues from whole-organ mapping bladder cancer specimens to reveal TERT mutational status, as well as to discern how tumors develop. Methods: Up to 23 tissues from nine whole-organ mapping bladder tumor specimens, were tested for TERT promoter mutations including tumor associated normal urothelium, non-invasive urothelial lesions (hyperplasia, dys-plasia, metaplasia), carcinoma in situ (CIS) and different areas of muscle invasive bladder cancers (MIBC). The mutational DNA hotspot region within the TERT promoter was analyzed by SNaPshot analysis including three hot spot regions (−57, −124 or −146). Telomere length was measured by the Relative Human Telomere Length Quantification qPCR Assay Kit. Results: TERT promoter mutations were identified in tumor associated normal urothelium as well as non-invasive urothelial lesions, CIS and MIBC. Analysis of separate regions of the MIBC showed 100% concordance of TERT promoter mutations within a respective whole-organ bladder specimen. Polyclonal events were observed in five out of nine whole-organ mapping bladder cancers housing tumor associated normal urothelium, non-invasive urothelial lesions and CIS where different TERT promoter mutations were found compared to MIBC. The remaining four whole-organ mapping bladders were monoclonal for TERT mutations. No significant differences of telomere length were observed. Conclusions: Examining multiple whole-organ mapping bladders we conclude that TERT promoter mutations may be an early step in bladder cancer carcinogenesis as supported by TERT mutations detected in tumor associated normal urothelium as well as non-invasive urothelial lesions. Since mutated TERT promoter regions within non-invasive urothelial lesions are not sufficient alone for the establishment of cancerous growth, this points to the contribution of other gene mutations as a requirement for tumor development.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Clonality; TERT promoter mutation; Whole-organ mapping bladder tumor

The tumor immune microenvironment drives a prognostic relevance that correlates with bladder cancer subtypes - Pfannstiel, Carolin; Strissel, Pamela; Chiappinelli, Katherine B.; Sikic, Danijel; Wach, Sven; Wirtz, Ralph M.; Wullweber, Adrian; Taubert, Helge; Breyer, Johannes; Otto, Wolfgang; Worst, Thomas; Burger, Maximilian; et al. (Cancer Immunology Research, 2019)
Muscle-invasive bladder cancer (MIBC) represents approximately two-thirds of invasive urothelial bladder cancers (UBC) and has high morbidity and mortality. Men are over 3-fold more frequently affected by UBC than women. Despite intensive efforts to improve patient treatment and outcome, two-thirds of patients with UBC will have a recurrence or disease progression within 5 years. We demonstrated that the quantity and spatial distribution of stromal tumor-infiltrating lymphocytes (sTIL) within the tumor immune microenvironment (TIME) predict stages of tumor inflammation, subtypes, and patient survival and correlate with expression of immune checkpoints in an analysis of 542 patients with MIBC. High sTILs indicated an inflamed subtype with an 80% 5-year DSS, and a lack of immune infiltrates identified an uninflamed subtype with a survival rate of less than 25%. A separate immune evading phenotype with upregulated immune checkpoints associated with poor survival. Within the TIME are tertiary lymphoid structures (TLS), which can mediate antitumor activity via immune cells. High TLS amounts and close tumor distance correlated significantly with an inflamed phenotype and favorable survival. The uninflamed and evasion phenotypes showed lowest TLS numbers, farthest tumor distances, and shortest survival. High inflammation also correlated with increased neoantigen load and mutational burden. Patients treated with adjuvant chemotherapy showed a favorable prognosis, which was dependent on high sTILs. Determination of sTILs and tumor subtypes may stratify therapy success and patient survival, and considering sTILs can easily be quantified using simple morphologic parameters, like hematoxylin and eosin, sTILs can be implemented for predicting patient survival in a routine manner.
CRIS-Team Scopus Importer:2019-06-21

Tumour immune microenvironment drives prognostic relevance correlating with bladder cancer subtypes - Eckstein, Markus; Strissel, Pamela; Pfannstiel, C.; Chiappinelli, K.; Sikic, D.; Wach, S.; Taubert, Helge; Wullich, Bernd; Keck, Bastian; Wirtz, R.; Breyer, J.; Burger, M.; et al. (VIRCHOWS ARCHIV, 2019)
CRIS-Team WoS Importer:2019-09-27

Uninflamed immunologic microenvironment of muscle-invasive bladder cancer associates with activating FGFR3 gene alterations. - Weyerer, Veronika; Stöhr, Robert; Strissel, Pamela; Strick, Reiner; Bolenz, Christian; Hartmann, Arndt; Erben, Philipp; Eckstein, Markus (CLINICAL CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2020-08-28

Unraveling the molecular pathways of DNA-methylation inhibitors: human endogenous retroviruses induce the innate immune response in tumors - Strick, Reiner; Strissel, Pamela; Baylin, Stephen B.; Chiappinelli, Katherine B. (OncoImmunology, 2016)
Loss of DNA methylation can activate endogenous retroviral expression and dsRNA in cancer cells. This leads to induction of toll-like receptor signaling stimulating an antiviral interferon response. Recent findings provide a therapeutic rationale for combining DNA methylation inhibitors with blockage of immune checkpoint proteins to fight cancer.
EVALuna2:33459